Reasons for the adoption of the Marshall Plan in modern Russian historiography - P.V. Teterin; N.S. Konev (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Background. The need to study issues related to the coverage of the reasons for the introduction of the Marshall Plan in domestic historiography is due to the weak degree of systematization and generalization of research results, which complicates the conceptu-alization of the problem. The purpose of the work is to analyze the problems of revealing the causes of the American policy of the Marshall Plan in the modern works of Russian historians. Materials and methods. Topical issues devoted to the scientific analysis of the views of modern Russian historians on the causes of the American Marshall Plan policy and the perception of it by domestic scientists (from the early 2000s to 2024) are consid-ered. In scientific work, the main subject is the consideration and analysis of content in the form of the following factors: economic, foreign policy and ideological. The methodologi-cal base is based on such methods as: comparative-historical, historical-typological, prob-lem-chronological. Results. The results of the study were obtained by analyzing the works of modern Russian historians on the main factors of the Marshall Plan. The results provide an opportunity to objectively study the Marshall Plan in the view of the modern historical community. Conclusions. The value of the conducted research lies in the fact that the find-ings can be applied to consider the issues and understand the essence of the conflict at the beginning of the Cold War, to study European integration processes and the role of the United States in this historical process. This article may be of interest to a wide audience, including historians, political scientists, economists and ordinary readers who are interested in the history of the Cold War and modern politics.